The Effect Of Rewards And Punishment On Employee Performance At ION Market Namlea - Rahma Satya Masna Hatuwe; Jumiyati Umasugi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
ABSTRACT This study aims to determine and analyze the effect of rewards and punishments on employee performance at Ion Market Namlea. The research method used was quantitative. The population in this study was all 24 Ion Market Namlea employees, using a saturated sampling technique. Data collection was conducted through a Likert-scale questionnaire. Data analysis used multiple linear regression with the assistance of SPSS version 22 software. The results showed that rewards have a positive and significant effect on employee performance. This means that the better the reward, the higher the employee performance. Punishment also has a positive and significant effect on employee performance, indicating that the application of firm and fair sanctions can improve discipline and work productivity. Simultaneously, rewards and punishment have a significant effect on employee performance at Ion Market Namlea, contributing 70.6%, with the remainder influenced by other factors outside this study.